Scoring analysis of the Men`s 2013 World Championship Tour of surfing - Farley, O.; Raymond, E.; Secomb, J.; Ferrier, B.; Lundgren, L.; Tran, T.; Abbiss, C.; Sheppard, J. (International Journal of Aquatic Research and Education, 2015)
The study compared scores obtained by the 10 highest and lowest ranked athletes on the men`s 2013 World Championship Tour (WCT) of surfing. Significant differences (p<.001) were identified between the two groups` average wave scores, average total scores and total heats competed. In addition, the average standard deviation (SD) of each surfer`s wave score was significantly different (p = .020) between the two groups. Significant moderate correlations were identified between athletes` average placing and the SD of their wave scores (r = .596, p = .006), and total heat scores (r=.474, p=.035). Repeated measures ANOVA also revealed significant differences between heat scores obtained during the final and all previous rounds (p < .001-.041). In conclusion, higher ranked surfers achieved higher wave scores and heat totals, and were more consistent in scoring. On average, a 1.04 point increase per wave score would allow a bottom 10 ranked surfer to reach the top 10, a small but impactful gain.